2016
DOI: 10.1016/j.jmii.2014.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Leishmania infection in a nonendemic area of South America

Abstract: American tegumentary leishmaniasis is the generic name for a variety of cutaneous and mucocutaneous presentations of parasitosis caused by several species of the genus Leishmania. This is a widespread infection in the American continent, from the South of the United States to the North of Argentina. We herein describe the management of a patient with American tegumentary leishmaniasis in Mendoza, Argentina, a nonendemic area of South America, whose diagnosis and treatment were significantly delayed, because th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Therefore, new protocols are needed to achieve a better efficacy in the prevention and clinical treatment, and they can include the relation of lipids released from parasites [1]. Different types of laboratory tests are available to diagnose parasitic infections, like conventional methods considered as gold standards and serological [48][49][50]. Several molecular diagnostic tools to detect parasites and new strains have been developed in the last decades [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, new protocols are needed to achieve a better efficacy in the prevention and clinical treatment, and they can include the relation of lipids released from parasites [1]. Different types of laboratory tests are available to diagnose parasitic infections, like conventional methods considered as gold standards and serological [48][49][50]. Several molecular diagnostic tools to detect parasites and new strains have been developed in the last decades [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Different types of laboratory tests are available to diagnose parasitic infections, like conventional methods considered as gold standards and serological [48][49][50]. Several molecular diagnostic tools to detect parasites and new strains have been developed in the last decades [48][49][50]. Accurate diagnosis of zoonotic infections collaborates with the work of medical scientists, policy makers and public health officials planning to prevent the dissemination of these diseases and establishing a world-wide network of surveillance for the coinfection of parasitic infections [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The use of minocycline in the treatment of malaria has shown a decrease in T-cell-mediated brain inflammation and a reduction in gene expression independent of the antiparasitic property ( 73 ). Nonetheless, a more recent study reported that a patient diagnosed with leishmaniasis was treated with minocycline ( 74 ). However, the treatment was stopped shortly after and nonconclusive results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…They are factors that trigger changes in the dynamics of the vector's dispersal, contributing to new establishments of the disease. For these reasons, provinces outside the endemic area of leishmaniasis have reported confirmed cases [36].…”
Section: Discussionmentioning
confidence: 99%